Evidence of heterogeneity in statin-associated type 2 diabetes mellitus risk: A meta-analysis of randomized controlled trials and observational studies. (May 2019) - Engeda, Joseph C.; Stackhouse, Ashlyn; White, Mary; Rosamond, Wayne D.; Lhachimi, Stefan K.; Lund, Jennifer L.; Keyserling, Thomas C.; Avery, Christy L.
Highlights: Statin users had higher risk of incident type 2 diabetes compared to non-users. Statin-associated risk of diabetes higher among observational studies. Heterogeneity observed by study design and among observational studies. Younger ages and lower cholesterol levels associated with higher incident diabetes. Abstract: Aims: To conduct a meta-analysis of statin-associated type 2 diabetes mellitus (T2D) risk among randomized controlled trials (RCTs) and observational studies (OBSs), excluding studies conducted among secondary prevention populations. Methods: Studies were identified by searching PubMed (1994-present) and EMBASE (1994-present). Articles had to meet the following criteria: (1) follow-up >one year; (2) >50% of participants free of clinically diagnosed ASCVD; (3) adult participants ≥30 years old; (4) reported statin-associated T2D effect estimates; and (5) quantified precision using 95% confidence interval. Data were pooled using random-effects model. Results: We identified 23 studies (35% RCTs) of n = 4, 012, 555 participants. OBS participants were on average younger (mean difference = 6.2 years) and had lower mean low-density lipoprotein cholesterol (LDL-C, mean difference = 20.6 mg/dL) and mean fasting plasma glucose (mean difference = 5.2 mg/dL) compared to RCT participants. There was little evidence for publication bias (P > 0.1). However, evidence of heterogeneity was observed overall and among OBSs and RCTs (PCochran  = <0.05). OBS designs, younger baseline mean ages, lower LDL-C concentrations, and high proportions of never or former smokers were significantly associated with increased statin-associated T2D risk. Conclusions: Potentially elevated statin-associated T2D risk in younger populations with lower LDL-C merits further investigation in light of evolving statin guidelines targeting primary prevention populations.